Comprehensive review on recycling of spent lithium-ion batteries. (2021) - Chandran, V.; Ghosh, Aritra; Patil, Chandrashekhar K.; Mohanavel, V.; Priya, A.K.; Rahim, Robbi; Madavan, R.; Muthuraman, U.; Karthick, Alagar
Abstract: Waste disposal of expended lithium-ion batteries enables recovery, recycling and reduction of greenhouse gas emissions. Complete discharge of electrochemical devices, especially release through electrode material and current collector (copper/aluminum foils). The release among electrode material particles, is the essential requirement for ensuring the energy yield of polymer electrolytes. In this work, existing technologies which used release electrode materials with spent lithium-ion batteries. Treating the underlying effects of lithium-ion battery oxidation is especially complex of the indirect pathways identified. Aging mechanisms are also divided into three degradation modes (DMs) for simplicity: loss of conductivity, a deficit of active material, and decline of lithium production. It's launched the lithium-ion secondary battery structure and assemblies outlined all forms of recycling processes from spent lithium-ion secondary batteries and provided some examples of common mixed recycling processes. Also, the problems and prospects of their recycling technology is discussed.